2015
DOI: 10.1073/pnas.1418840112
|View full text |Cite
|
Sign up to set email alerts
|

Bestrophin 1 is indispensable for volume regulation in human retinal pigment epithelium cells

Abstract: In response to cell swelling, volume-regulated anion channels (VRACs) participate in a process known as regulatory volume decrease (RVD). Only recently, first insight into the molecular identity of mammalian VRACs was obtained by the discovery of the leucine-rich repeats containing 8A (LRRC8A) gene. Here, we show that bestrophin 1 (BEST1) but not LRRC8A is crucial for volume regulation in human retinal pigment epithelium (RPE) cells. Whole-cell patch-clamp recordings in RPE derived from human-induced pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
142
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(159 citation statements)
references
References 45 publications
9
142
0
4
Order By: Relevance
“…[7][8][9] Monomers of Best1 oligomerize [10][11][12][13][14] to form a highly conserved homopentameric Ca 2þ -activated ion channel. 8,9 Data from heterologous systems, 15,16 primary human RPE cell culture, 17,18 mouse models, 19,20 the structurally similar paralog bestrophin-2, 21,22 as well as recently published crystal structures 8,9 all unambiguously demonstrate that mammalian Best1 is a calcium-activated anion channel. In addition to functioning as an anion channel, Best1 regulates intracellular Ca 2þ signaling and influences Ca 2þ homeostasis.…”
Section: Discussionmentioning
confidence: 80%
“…[7][8][9] Monomers of Best1 oligomerize [10][11][12][13][14] to form a highly conserved homopentameric Ca 2þ -activated ion channel. 8,9 Data from heterologous systems, 15,16 primary human RPE cell culture, 17,18 mouse models, 19,20 the structurally similar paralog bestrophin-2, 21,22 as well as recently published crystal structures 8,9 all unambiguously demonstrate that mammalian Best1 is a calcium-activated anion channel. In addition to functioning as an anion channel, Best1 regulates intracellular Ca 2þ signaling and influences Ca 2þ homeostasis.…”
Section: Discussionmentioning
confidence: 80%
“…However, while LRRC8A is a crucial element of volume regulation in some cell lines, it is less important for VRAC and RVD in others. In fact, it might even be irrelevant for VRAC and volume regulation in retinal pigment epithelial cells Milenkovic et al 2015). At any rate, shortly after LRRC8A had been reported as VRAC, a study reported the role of LRRC8A in cisplatin resistance (Sorensen et al 2014).…”
Section: Lrrc8: CL − Channels In Charge Of Volume Regulation and Apopmentioning
confidence: 99%
“…Nearly 200 mutations in BEST1 have been associated with retinal degenerative disorders, and the vast majority of those that have been characterized cause Cl − channel dysfunction (7)(8)(9)(10)(11). Studies have also indicated that certain bestrophin channels are important for cell volume regulation (12)(13)(14).…”
mentioning
confidence: 99%